Investigation of peripheral photoplethysmographic morphology changes induced during a hand-elevation study - Hickey, Michelle; Phillips, Justin P.; Kyriacou, Panayiotis A. (Journal of clinical monitoring and computing, 2016)
A hand-elevation study was carried out in the laboratory in order to alter peripheral blood flow with the aim of increasing understanding of factors affecting the morphology of peripheral photoplethysmographic signals. Photoplethysmographic (PPG) signals were recorded from twenty healthy volunteer subjects during a hand-elevation study in which the right hand was raised and lowered relative to heart level, while the left hand remained static. Red and infrared (IR) PPG signals were obtained from the right and left index fingers using a custom-made PPG processing system. PPG features were identified using a feature-detection algorithm based on the first derivative of the PPG signal. The systolic PPG amplitude, the reflection index, crest time, pulse width at half height, and delta T were calculated from 20 s IR PPG signals from three positions of the right hand with respect to heart level (−50, 0, +50 cm) in 19 volunteers. PPG features were found to change with hand elevation. On lowering the hand to 50 cm below heart level, ac systolic PPG amplitudes from the finger decreased by 68.32 %, while raising the arm increased the systolic amplitude by 69.99 %. These changes in amplitude were attributed to changes in hydrostatic pressure and the veno-arterial reflex. Other morphological variables, such as crest time, were found to be statistically significantly different across hand positions, indicating increased vascular resistance on arm elevation than on dependency. It was hypothesized that these morphological PPG changes were influenced by changes in downstream venous resistance, rather than arterial, or arteriolar, resistance. Changes in hand position relative to heart level can significantly affect the morphology of the peripheral ac PPG waveform. These alterations are due to a combination of physical effects and physiological responses to changes in hand position, which alter vascular resistance. Care should be taken when interpreting morphological data derived from PPG signals and methods should be standardized to take these effects into account.